Mathematical Modeling of Leachate in Landfills: Overview and Application - Achmad Fahrurozi; Kartono Kartono; Sunarsih Sunarsih (Journal of Fundamental Mathematics and Applications (JFMA), 2026)
The Jatibarang Final Processing Site (TPA) plays a crucial role as a domestic waste treatment unit for the Semarang City area. Accumulated domestic waste generates leachate, which typically contains toxic chemicals, pathogenic bacteria, as well as organic and inorganic compounds. Uncontrolled management of domestic waste can lead to severe environmental impacts, such as the spread of diseases and the degradation of water quality, which may hinder potential reuse. It is essential for TPA management to monitor leachate concentration distribution to facilitate effective mitigation efforts. The phenomena and challenges associated with TPAs can be examined through mathematical modeling particularly dynamic models to study the behavior of leachate dispersion. Numerical approaches, especially the finite difference method, play a significant role in solving the complexity of models that are otherwise analytically intractable. This article presents a study based on field observations and a review of relevant scientific literature to identify the various potentials and challenges related to leachate dispersion, analyzed through mathematical modeling and numerical techniques.